Socialization of Gender Education in Family According to Islamic Perspective - Nur Azwani Mansor (Rabbanica: Journal of Revealed Knowledge)
This article discusses the process of socialization of gender education in the family according to Islamic concepts and values. The role of the family is emphasis in order to have better understanding on gender education and children's perceptions on gender differences between men and women. This study employs a qualitative methodology and examines primary materials, including the Quran,the hadiths, and pertinent Islamic literature. A thorough examination of the family's duties and responsibilities in teaching children within the framework of gender is carried out. From an Islamic standpoint, the family is the primary socialization agent. The primary agents that aid in the socialization process are family members, including parents, siblings, brothers, and closest relatives. This method is used in childhood to shape thoughts and behaviour as well as to teach children ways to act in particular scenarios or in adulthood. Children cannot adapt or behave in a way that aligns with Islamic law if they do not receive an adequate and effective gender socialisation experience. The greatest methods and techniques for providing children with a fair and balanced gender education are discussed in this article and can be adopted by parents and families. According to the analysis, gender education should be prioritized by families from an early age in order to help the children develop a good view of gender and prepare them for adulthood in the traditional gender roles. This paper concludes by offering a holistic and integrated viewpoint on gender education socialization inside the home from an Islamic standpoint. It offers helpful advice and guidelines that families and communities can apply to create a gender-neutral society founded on Islamic religious teachings.In conclusion, this article provides a holistic and integrated view of the socialization of gender education in the family according to an Islamic perspective. It provides practical guidance and principles that can be used by families and communities to build a gender-harmonious society based on Islamic religious teachings.